DETERMINANTS OF CONTRACEPTIVE USE IN NTB PROVINCE BASED ON THE 2019 SKAP DATA ANALYSIS - Sudarmi Sudarmi; Linda Meliati; Siti Halimatussyaadiah (Universitas Airlangga, 2023)
Prevention of pregnancy by various contraceptive methods remains an important part of medical practice and can occur during any reproductive cycle. The more types of contraceptive methods available, the more choices of contraceptive methods available for people. Many determinant factors cause women of childbearing age to choose contraceptives that suit their needs. This study aims to determine the determinants affecting women of childbearing age using contraceptives in West Nusa Tenggara Province. The design of this study is an analytical study (descriptive analysis) with a cross-sectional approach using secondary data from the 2019 SKAP Family Planning and Family Development Population Accountability Performance Survey (KKBPK) in the Province of West Nusa Tenggara (NTB). Data were analyzed using bivariate analysis using Chi-Square and multivariate with logistic regression. The results showed that the determinants that affect women of childbearing age in using contraceptive methods include: unmet need, age, parity, previous family planning experience, decision-making, knowledge, and visits to health facilities. The results of multivariate analysis of the most dominant decision-making factors influencing the use of contraceptive methods in women of childbearing age with an OR value of 174,666. It can be interpreted that the decision-making ability of women of childbearing age is 174,666 times more influencing the use of contraceptive methods compared to other variables. This study recommends empowering women of childbearing age through increasing knowledge by maximizing the individual counseling process so that women of childbearing age can choose contraceptive methods according to their needs.